Acute Increase of Renal Perfusion Pressure Causes Rapid Activation of mTORC1 (Mechanistic Target Of Rapamycin Complex 1) and Leukocyte Infiltration. Issue 6 (16th March 2022) - Shimada, Satoshi; Yang, Chun; Kumar, Vikash; Mattson, David L.; Cowley, Allen W.
Abstract : Background: The present study in Sprague-Dawley rats determined the effects of a rapid rise of renal perfusion pressure (RPP) upon the activation of mTOR (mechanistic target of rapamycin), and the effects upon the infiltration of CD68-positive macrophages/monocytes and CD3-positive T lymphocytes into the kidneys. Methods: RPP was elevated by 40 mm Hg for 30 minutes in male Sprague-Dawley rats while measuring renal blood flow and urine flow rate. Sham rats were studied in the same way, but RPP was not changed. Since initial studies found that the acute increase of RPP resulted in activation of mTORC1 (phosphorylation of S6 S235/236 ), the effects of inhibition of mTORC1 with rapamycin pretreatment were then determined. Results: It was found that a 30-minute increase of RPP (≈40 mm Hg) resulted in an 8-fold increase of renal sodium excretion which was blunted by rapamycin treatment. Renal blood flow was not affected by the elevation of RPP. Activation of mTORC1 was observed. Significant increases in CD68-positive macrophages were found in both the cortex (intraglomerular and periglomerular regions) and in the outer medullary interstitial regions of the kidney and prevented by rapamycin treatment. Increases in CD3-positive T lymphocytes were observed exclusively in the periglomerular regions and prevented by rapamycin treatment. Upregulation of several proinflammatory markers was observed. Conclusions: We conclude that elevation of RPP rapidly activates mTORC1 resulting in infiltration of immune cells into the kidney.